The Relationship Between Interpregnancy interval and Incomplete Abortion: A Case-Control Study: Hubungan Jarak Kehamilan Dengan Kejadian Abortus Inkomplit: Case Control Study - Lestari, Dian Rosmala; Hamudi, Juli Purnama (Napande: Jurnal Bidan, 2025)
Incomplete abortion is one of the pregnancy complications that can pose serious health risks to the mother if not managed properly. Several risk factors can influence the occurrence of incomplete abortion, such as interpregnancy interval, parity, occupation, history of abortion, and maternal age (<20 years or >35 years). This study aimed to examine the association between interpregnancy interval and the incidence of incomplete abortion. A case-control study design was employed at Dewi Sartika Hospital in Kendari City in 2024. The population included all mothers who experienced abortion and were recorded in the hospital registry from 2021 to 2023, totaling 204 individuals. Samples were selected using random sampling with matching based on respondents’ education level, with a 1:1 ratio, resulting in 102 cases and 102 controls. Secondary data were collected using a checklist form and analyzed using the Chi-Square test. The results showed a significant relationship between interpregnancy interval and incomplete abortion, with a p-value of 0.007 (p < 0.05). The odds ratio (OR) was 2.567, indicating that mothers with a non-ideal interpregnancy interval had a 2.5 times higher risk of experiencing incomplete abortion compared to those with an ideal interval.